Effect of Feeding Quails with Mixture Feeds Composed of Crab Waste Meal, Leubim Fish Waste Meal, and Broken Rice Grains as Partly Substitution of Commercial Diet on Egg Quality - Zulfan Zulfan; Herawati Latif; Cut Aida Fitri; Evi Aswita (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2020)
In rearing quails, many attempts have been done to reduce feed cost among other things by replacing partly commercial diet with numerous alternative feed sources such as crab waste meal (CWM), leubim fish (Canthidermis maculata) waste meal (LFWM), and broken rice grains (BRG). The purpose of this study was to determine the effect of using a mixture feeds composed of CWM + LFWM + BRG as a substitute for commercial laying chicken diets on the quality of quail eggs. This research was conducted at the Field Laboratory of Animal Husbandry and the Laboratory of Poultry Production Science, Syiah Kuala University. This study used 80 female quails (Coturnix-coturnix japonica) females aged 4 weeks. The treatment was feeding quails with the commercial diet of laying hen (324-1M) of which 0, 10, 20, and 30% of the diets was substituted by the mixture feeds composed of CWM + LFWM + BRG. The study was performed into block randomized design (BRD) consisting of 4 treatments and 4 replicate blocks. The blocks were established based on the different initial body weights of 4-week ages of female quails. Each treatment was an experimental unit consisting of 5 female quails each. The measured parameters were Yolk Index (YI), yolk color, Albumen Index (AI), eggshell thickness, and egg weight. The results of the study indicated that using up to 30% mixture feeds composed of 7,5% CWM + 9,1% LFWM + 13,4% BRG as a substitute for commercial laying chicken diets most significantly increased yolk index and yolk color of quail eggs. However, the albumen index, eggshell thickness, and egg weight were not significantly affected.